Whole genome sequencing of live attenuated Leishmania donovani parasites reveals novel biomarkers of attenuation and enables product characterization - Sreenivas Gannavaram (Nature Portfolio, 2017)
Abstract No licensed human vaccines are currently available against leishmaniasis. Several anti-leishmanial vaccines are currently undergoing testing, including genetically modified live-attenuated parasite vaccines. Studies with live attenuated Leishmania vaccines such as centrin deleted Leishmania donovani parasites (LdCen −/−) showed protective immunity in animal models. Such studies typically examined the biomarkers of protective immunity however the biomarkers of attenuation in the parasite preparations have not received adequate attention. As several candidate vaccines enter clinical trials, a more complete product characterization to enable maintenance of product quality will help meet regulatory requirements. Towards this goal, we have determined the complete genome sequence of LdCen −/− and its parent strain Ld1S-2D (LdWT) and characterized the LdCen −/− vaccine strain using bioinformatics tools. Results showed that the LdCen −/− parasites, in addition to loss of the centrin gene, have additional deletions ranging from 350 bp to 6900 bp in non-contiguous loci on several chromosomes, most commonly in untranslated regions. We have experimentally verified a subset of these adventitious deletions that had no impact on the attenuation of the LdCen −/− parasites. Our results identified hitherto unknown features of attenuation of virulence that could be used as markers of product quality in production lots and highlight the importance of product characterization in parasitic vaccines.